Is Agriculture a National or County Governments’ Policy Function in Kenya? Interrogating Section 4 of the AFA Act together with the Fourth Schedule and Article 191 of the Constitution (Strathmore Law Review, 2019)
As the people of Kenya witnessed the promulgation of the 2010 Constitution, there was so much hope and faith in the atmosphere for a better tomorrow. One of the main reasons for this was the entrenchment of devolution which was expected to lead to better service delivery and promote self-governance. However, almost a decade down the line, the expectations of the people have not been met. The effectiveness of devolution is largely dependent on the nature and extent of powers exercised by the counties and the functions they perform. The Fourth Schedule of the Constitution outlines the functions of the national and county governments. However, some functions such as agriculture seem to overlap. The national government’s function with regards to agriculture is ‘policy’. The same is true for county governments. The national government, through parliament, has enacted a law, the Agriculture and Food Authority Act (AFA Act), which this study finds to have encroached on the functions of county governments. To demonstrate this, the study relies on Article 191 of the Constitution, which is on conflict of laws; on literature review and comparative jurisprudence.